2017
DOI: 10.1093/gerona/glx100
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Disability in Different Combinations of Somatic and Mental Multimorbidity

Abstract: Depression and/or cognitive impairment was identified in one-third of older adults with multimorbidity, and these combinations were associated with substantially greater prospective disability than combinations comprised exclusively of somatic conditions. This argues for identifying and managing mental health conditions that co-occur with somatic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 25 publications
5
49
0
Order By: Relevance
“…Later studies including four cross-sectional and two cohort studies with 1 and 2 years follow-up time have also found associations between multimorbidity and ADL/IADL disability [34][35][36][37][38]. It may seem that disease combinations including depression and cognitive impairment increase the risk for ADL/IADL disability substantially compared to combinations of only somatic disease [37,39]. Other studies have found associations between the number of chronic conditions and function in both basic and instrumental activities of daily living [18,40,41].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Later studies including four cross-sectional and two cohort studies with 1 and 2 years follow-up time have also found associations between multimorbidity and ADL/IADL disability [34][35][36][37][38]. It may seem that disease combinations including depression and cognitive impairment increase the risk for ADL/IADL disability substantially compared to combinations of only somatic disease [37,39]. Other studies have found associations between the number of chronic conditions and function in both basic and instrumental activities of daily living [18,40,41].…”
Section: Discussionmentioning
confidence: 98%
“…A systematic review from 2015 concluded that multimorbidity predicts future functional decline in adults, but comparisons between studies are hampered by the heterogeneity in definitions and operationalizations of multimorbidity and functional decline and the included cohort studies had short follow-up time (1-3 years) [9]. Later studies including four cross-sectional and two cohort studies with 1 and 2 years follow-up time have also found associations between multimorbidity and ADL/IADL disability [34][35][36][37][38]. It may seem that disease combinations including depression and cognitive impairment increase the risk for ADL/IADL disability substantially compared to combinations of only somatic disease [37,39].…”
Section: Discussionmentioning
confidence: 99%
“…Recent advancements provide clinical insights into the functional consequences of specific multimorbidity combinations with diabetes. 1,2,11,35,36 This knowledge is essential in order to design interventions and optimize the clinical care for patients with diabetes-multimorbidity. 8 Our research highlights the importance of depressive disorders and stroke within larger multimorbidity combinations in patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Because the identification of all multimorbidity permutations is infeasible and potentially uninformative, examining prevalent and clinically meaningful chronic diseases remains the recommended approach. 2,[9][10][11] Overall, individuals with multimorbidity are more likely to develop functional limitations leading to premature disability and death, and specific combinations may signal high disability burdens. 12 The purpose of our study is to evaluate the association between prevalent diabetes-multimorbidity combinations and prospective disability in a nationally representative sample of middle-aged and older Americans.…”
Section: Introductionmentioning
confidence: 99%
“…According to analyses of data from the SNAC‐K population‐based study, neuropsychiatric diseases, alone or in association with each other, are major determinants of disability and slow walking speed in older adults, whereas isolated cardiovascular multimorbidity is associated only with a decline in walking speed . Other longitudinal study results support these findings .…”
Section: Interplay Between Multimorbidity and Functionmentioning
confidence: 97%